Rancang Bangun Aplikasi Pencatatan Rekam Medis Pada Unit Rawat Jalan di Rumah Sakit Assakinah Medika Sidoarjo - Indrawati, Yuni; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Medical records are factual documents which related to patient condition, past and present treatment which is written by a doctor who treat the patient. (Huffman, 1999).RSAM have a diffcult situation to search, provide, and study patient medical records at Outpatient Unit because all of them are still in document format in archive room which could make it take a long time to deliver it to the admin room.To help solve this difficulty, therefore the hospital needs a medical records application at outake patient unit. This application is made to help doctors to decide what action to the patient so it will produce accurate and easy to search medical records. With the help of this application in Outpatient Unit, so Outpatient Unit at RSAM will become better and faster to give a service to the patient according to hospital service standard.With design and development of medical records application at outpatient unit in RSAM will produce a report and also medical record information about patient visitation, medical record registration, and income. This system is used by doctor to consider what action should be taken and trail access of patient medical records.